2019
DOI: 10.13057/biodiv/d210137
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of SSR and important agronomical characters of promising mutant lines of soybean

Abstract: Abstract. Asadi, Dewi N, Nugroho K, Terryana RT, Mastur, Lestari P. 2020. Evaluation of SSR and important agronomical characters of promising mutant lines of soybean. Biodiversitas 21: 299-310. Improved soybean (Glycine max (L.) Merr.) varieties resistant to major pest or disease, and in accordance with consumer preferences are important in breeding programs to raise their productivity. Identification of superior promising mutant lines of soybean before releasing them needs multiple environment trials compleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…The advantage of the Biosoy variety is that it has larger seeds, reaching ± 21.74 gr/100 seeds than Anjasmoro. in line with research [14] which produced larger seed sizes for the Biosoy variety (22 g/100 seeds) than the Anjasmoro varieties (15 g/100 seeds) and Grobogan (21 g/100 seeds). The potential production of the Biosoy variety is 3.55 tons ha -1, and the average production is 2.7-3 tons ha -1 .…”
Section: The Advantages Of Early-maturity Soybean Varietiessupporting
confidence: 87%
See 1 more Smart Citation
“…The advantage of the Biosoy variety is that it has larger seeds, reaching ± 21.74 gr/100 seeds than Anjasmoro. in line with research [14] which produced larger seed sizes for the Biosoy variety (22 g/100 seeds) than the Anjasmoro varieties (15 g/100 seeds) and Grobogan (21 g/100 seeds). The potential production of the Biosoy variety is 3.55 tons ha -1, and the average production is 2.7-3 tons ha -1 .…”
Section: The Advantages Of Early-maturity Soybean Varietiessupporting
confidence: 87%
“…The Biosoy soybean variety has the advantage of early maturity to minimize drought and has large seeds according to farmer preferences [13], making it suitable for introduction to farmers. Several studies have shown that Biosoy soybean production is higher than existing varieties, such as the Anjasmoro, Grobogan, Dena, and other varieties [14,15]. Anjasmoro is the existing variety that is most widely planted by farmers in Indonesia [16].…”
Section: Introductionmentioning
confidence: 99%
“…The significant differences for the different traits scored on the accessions indicate the existence of variability in the selected population that can be exploited for an improved breeding program. Trait variability facilitates trait-assisted selection of best lines for improvement (Moradi et al, 2019;Dewi et al, 2020). Various studies have shown GEI effect on several crops, such as Rice (Rahman and Shah, 2019;Calayugan et al, 2020), sweet potato (Ngailo et al, 2019), and Sorghum (Jiang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These are, however, further seen in the effects of various locations where they are cultivated. Therefore, morphological characterization in various locations assists breeders in selecting superior lines for further improvement (Peratoner et al, 2016;Moradi et al, 2019;Dewi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular markers have been used very frequently in ecological, taxonomical, diversity, conservation, phylogenic and genetic studies amongst organisms (Avise 1994;Weising et al 2005;Sheth and Thaker 2017;Srivastava et al 2020). After the advent of Polymerase chain reaction (PCR) several advancements and introduction of new concepts were employed in the improvement of various types of molecular marker technologies like amplified fragment length polymorphism (AFLP) (Vos et al 1995;Roncallo et al 2019), inter simple sequence repeats (ISSRs), (Vanijajiva 2012;Husnudin et al 2019), random amplified polymorphic DNA (RAPD) (Vanijajiva et al 2005;Ihwan and Hakim 2019), Simple Sequence Repeats (SSR (Dewi et al 2020), Single Sequence Polymorphism (SNP) (Trick et al 2009;Luo et al 2010;Bayerl et al 2018). For distinct genetic applications amongst diverse plant species, different markers have been used by various researchers in commercial fruit accessions.…”
Section: Introductionmentioning
confidence: 99%